New Conceptualizations of Language Aptitude - The Potential of Working Memory in Second Language Acquisition (SLA) - Grymska, Beata (Theory and Practice of Second Language Acquisition, 2016)
The chapter sheds light on new conceptualizations of foreign language aptitude by emphasizing the role of working memory (WM). It is organised into 3 sections. The first section presents a brief historical overview of the research on language aptitude based on John Carroll’s work. The second part elaborates on working memory construct discussing Baddeley’s multi-component model of WM and its functions. The paper proposes incorporating working memory as a crucial component of language aptitude construct. In the light of the issue mentioned above, the third section of the article focuses on the newest and original empirical evidence which supports the role of WM in different aspects of L2 learning, i.e. reading, listening, speaking, writing and bilingual interpretation as well as vocabulary and grammar learning. Its concluding part reflects upon the relevance of language aptitude paving the way for future research.